Re-Imagining High-Density Mixed-Use Streets - Somi Sareen; Mazharul Haque (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
This paper analyses the essential role of mixed-use streets in contemporary cities and addresses their inherent issues. The study highlights the national policy focus on mixed-use streets, which can improve sustainability, economic development, social integration, and quality of life. Due to divided responsibilities, traffic prioritization, and changes in the commercial sector, mixed-use streets are sometimes neglected. The study reviews mixed-use street patterns in Okhla, an unplanned, high-density area; examining how population density and urban activities affect streets, focusing on its imprecise definition and seeming popularity. An extensive case study reveals the lack of specific zoning standards, poor planning provisions, and low network density along with traffic congestion, space encroachment, and a lack of public spaces. The author proposes merging multivariable densities and using network density to portray urban structure. The findings contribute to sustainable urban development discussions and help policymakers and planners improve mixed-use spaces' livability and functionality.